Combined Overexpression of JARID2, PRDM14, ESRRB, and SALL4A Dramatically Improves Efficiency and Kinetics of Reprogramming to Induced Pluripotent Stem Cells. (26th November 2015) - Iseki, Hiroyoshi; Nakachi, Yutaka; Hishida, Tomoaki; Yamashita‐Sugahara, Yzumi; Hirasaki, Masataka; Ueda, Atsushi; Tanimoto, Yoko; Iijima, Saori; Sugiyama, Fumihiro; Yagami, Ken‐Ichi; Takahashi, Satoru; Okuda, Akihiko; et al.
Abstract : Identification of a gene set capable of driving rapid and proper reprogramming to induced pluripotent stem cells (iPSCs) is an important issue. Here we show that the efficiency and kinetics of iPSC reprogramming are dramatically improved by the combined expression of Jarid2 and genes encoding its associated proteins. We demonstrate that forced expression of JARID2 promotes iPSC reprogramming by suppressing the expression of Arf, a known reprogramming barrier, and that the N‐terminal half of JARID2 is sufficient for such promotion. Moreover, JARID2 accelerated silencing of the retroviral Klf4 transgene and demethylation of the Nanog promoter, underpinning the potentiating activity of JARID2 in iPSC reprogramming. We further show that JARID2 physically interacts with ESRRB, SALL4A, and PRDM14, and that these JARID2‐associated proteins synergistically and robustly facilitate iPSC reprogramming in a JARID2‐dependent manner. Our findings provide an insight into the important roles of JARID2 during reprogramming and suggest that the JARID2‐associated protein network contributes to overcoming reprogramming barriers. Stem Cells 2016;34:322–333